Answers

  • Brainly User
2015-05-16T09:44:55+05:30
11x - 7y =xy  be first equation 
9x   - 4y = 6xy be second equation 
use elemination method to find the values of x and y 
11x - 7 y = xy  multiply this equation by 6  we get
66x - 42 y = 6xy 
now come to the other equation 
9x - 4y = 6xy  multiply this equation  by 1 for making the xy same  we get  
9x - 4y = 6xy 
use these equation and subtract it
66x - 42y = 6xy 
9x   -  4y  =6 xy 
-      +         - 
57x - 38y  = 0 
57 x = 38 y 
x= 38y /57 
substitute this equation in equation second
9x - 4y =  6xy 
9*38y/57  - 4y = 6*38y²/57
now divide this equation by y to get the y equal in all 
9*38/57 - 4 = 6*38y/57 
342 - 228  = 6×38y
114=6*38y 
57 =3*38 y
y=29/38
but this value in equation 57x = 38 y 
57x = 38*57/38 *3 
57x =57/3 
x=1/3
by this we get the value of x and y 

y=29/38  ,x=1/3
1 5 1